Examining the impact of total rewards on proactivity among Chinese knowledge employees: the moderating role of vertical and horizontal collectivist orientations - Zhou, Jie; Yang, Junqing; Faye, Bonoua (Frontiers in Psychology, 2025)
IntroductionIn practice, the phenomenon of employees “lying flat”—characterized by poor proactive behavior—reflects a failure in the organization’s compensation incentive policy. Currently, the most effective compensation practice is total rewards, yet previous research seems to overlook the impact of total rewards (TR) on proactivity and has not considered when its effects may vary across different forms of proactive behavior.MethodsBased on social exchange theory and role theory, this study uses hierarchical regression and self-help methods to conduct a two-wave survey of the new generation of Chinese knowledge employees (N = 336).ResultsThe results show that total rewards significantly enhance both individual task proactivity and team member proactivity, with a greater positive effect on the former. Additionally, the study finds that vertical collectivism orientation weakens the total rewards-individual task proactivity relationship, while horizontal collectivism orientation weakens the total rewards-team member proactivity relationship. Surprisingly, the study does not support a positive moderating effect of vertical collectivism orientation on total rewards-team member proactivity or horizontal collectivism orientation on total rewards-individual task proactivity.DiscussionOur findings contribute to a deeper understanding of the effectiveness of compensation practices through the lens of intracultural heterogeneity and provide valuable insights for managers seeking to foster various forms of proactivity among the new generation of knowledge employees.